2021
DOI: 10.1136/bmj.n608
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence to the test, trace, and isolate system in the UK: results from 37 nationally representative surveys

Abstract: Objective To investigate rates of adherence to the UK’s test, trace, and isolate system over the initial 11 months of the covid-19 pandemic. Design Series of cross sectional online surveys. Setting 37 nationally representative surveys in the UK, 2 March 2020 to 27 January 2021. Participants 74 697 responses from 53 880 people living in the UK, aged 16 years or ol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
274
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(300 citation statements)
references
References 25 publications
17
274
8
1
Order By: Relevance
“…Previous research indicates that knowledge of COVID-19 symptoms among the UK public is low, with only about half able to identify all three main symptoms (4,16). In our study, while recognition of symptoms was reasonably good, it was clear that recognition alone was not always sufficient to trigger a decision to seek a test.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that knowledge of COVID-19 symptoms among the UK public is low, with only about half able to identify all three main symptoms (4,16). In our study, while recognition of symptoms was reasonably good, it was clear that recognition alone was not always sufficient to trigger a decision to seek a test.…”
Section: Discussionmentioning
confidence: 99%
“…Data from behavioural surveys in England show only 51% of participants knew the symptoms that testing is recommended for, only 18% sought testing if they had the symptoms and only 42.5% fully adhered to self-isolation. Engagement was lower in younger people and amongst those in financial hardship 12 . Engagement with population level asymptomatic testing using lateral flow testing has also been shown to be low, particularly in socioeconomically disadvantaged areas 13 .…”
Section: Discussionmentioning
confidence: 93%
“…March 18, 2020, in 24 Survey data from the United Kingdom found that non-adherence to public health guidelines for patients with COVID-19 was associated with factors including dependent children in the household, lower socioeconomic status, and being an essential worker. 25 Financial support, and wrap around services, are in particular associated with improved ability to self-isolate. 25,26 Figure 2 shows risk factors for influenza-like illness among a nationally representative sample of 2,042 adults from the United States during the H1N1 influenza pandemic in 2009.…”
Section: Evidence For the Effectiveness Of Paid Sick Leavementioning
confidence: 99%
“…25 Financial support, and wrap around services, are in particular associated with improved ability to self-isolate. 25,26 Figure 2 shows risk factors for influenza-like illness among a nationally representative sample of 2,042 adults from the United States during the H1N1 influenza pandemic in 2009. 27 Inability to work from home and absence of paid sick leave were associated with an approximately 50% increase in the risk of influenza-like illness.…”
Section: Evidence For the Effectiveness Of Paid Sick Leavementioning
confidence: 99%